Low-frequency impedance spectroscopy of polymers and crystals with a hydrogen-bond network. Quantum collective excitations of nuclei in molecules - O.D. Novik; N.D. Gavrilova; O.V. Malyshkina (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2024)
In this work, we present the results of our studies of temperature-frequency behaviour of dielectric permittivity ε, conductivity σ, relaxation time τμ, thermodepolarisation currents j, and pirocurrents γ in hydrophilic polymers and crystals with a hydrogen-bond network OH…O in the ranges of 0,01–107 Hz and 20-140°С. Analysis of the obtained data has revealed temperature anomalies of ε(T), σ(T), τμ(T), j(T), and γ(T) around «threshold» points at 20, 36, 50, 65, and 85°С, where the destruction of water clusters (and, if above 100°С, of water molecule itself) takes place, and thereby the release of deep traps, the change of the charge carriers (Н3O+, ОН–, etc.) composition and of their trajectories in volume are observed. In this study, we draw an analogy between the temperature behaviour of ε, σ, τμ, j, and γ in «threshold» points having a characteristic single resonance peak and the dipole resonance of photoabsorption in clusters of Ag, Mg, and Sm metals, which is manifested in the broadening of resonance, single peak splitting, and in the formation of single-domain ATGS+Cr3+ crystal (0,06 wt.% Cr). We also discuss a possible onset of collective nuclear excitements during irradiation with photons or an onset of internal electrical displacement field Edp in a sudden sample cooling or warming. The entanglement of photons by polarization is also considered.